Desenvolvimento de um goniômetro virtual - Vale, Renno de Ervedosa Diniz (2018)
The goniometer is a widely used tool in the rehabilitation process of injured limbs. Its application however, implies a number of negative factors that could be minimized if such tool were replaced. The proposal of this work is to develop an alternative tool to the goniometer that will minimize the recurring problems brought by it. To achieve these goals, a Leap Motion device will be used in communication with a common computer. To complete the work, a test model will be developed to commit the application developed to an initial validation through comparisons between measurements of the new tool developed and measurements of the goniometer.